HYPERBOLE IN MELANIE MARTINEZ’S “K-12” ALBUM - Dwi Nitisari; Raisa Fadhillah; Indah Lestari (UG Journal, 2022)
The purposes of this research are to describe the types of hyperbole found in Melanie Martinez's K-12 and to find out the most dominant type of hyperbole found in Melanie Martinez's K-12. Claudia Claridge's Hyperbole theory is used to analyze the type of hyperbole meanwhile descriptive qualitative method is used for the method of the reseach. After classifying and analyzing the data, it is found45 data of hyperbolic expressions which are categorized into seven categories namely single-word hyperbole, phrasal hyperbole, clausal hyperbole, numerical hyperbole, superlative hyperbole, comparison, and repetition. At the end of analyzing, clausal hyperbole is found as the most dominant type of hyperboleused.